Development of back side technology for light trapping and photon recycling in GaAs solar cells. (12th October 2018) - Micha, Daniel Neves; Höhn, Oliver; Oliva, Eduard; Klinger, Vera; Bett, Andreas W.; Dimroth, Frank
Abstract: In this work, we propose and realize three different design strategies to implement an optical cavity in GaAs thin film solar cells in order to confine its internal luminescence and hence to exploit photon recycling. The strategies are based on the definition of a highly reflective and very conductive back side, whereas front side light extraction is limited by total internal reflection. We show characterization results on the internal reflectivity of the back reflector and on the contact resistance at the rear side, important quantities for a good functioning of the final solar cell. First, a back side using only metal was optimized with a pure Ag layer leading to an internal reflectivity of 95.2% and a contact resistance of 1.0 × 10 −4  Ω for a 1 cm 2 device. With a metal‐dielectric stack at the back side and electrical contacts made by metals via point‐contacts, a second approach led to averaged internal reflectivity of 98.0% and contact resistance of 1.8 × 10 −4  Ω for a 1 cm 2 device. A third strategy in which a transparent conductive oxide in combination with a metal layer was used did not show the expected results in optical and electrical properties. We fabricated and characterized solar cells with the most promising back sides. When comparing with an ordinary reference GaAs solar cell, external radiative efficiency increased by factors of 150% and 90% for the thin film solar cells with pure Ag and with the metal‐dielectric stack at the back side, allowing enhancements of 19 and 13 mV in V OC, respectively. Abstract : In this work, we propose and realize different design strategies for exploitation of photon recycling in GaAs solar cells. The proposals rely on the formation of a reflective and conductive back side to be defined in a thin film device. With two of the proposed strategies applied to the final solar cells, it was possible to show systematic increases in the external radiative efficiency ( ERE ) that led to enhancements in open circuit voltage ( V OC ) and finally to higher efficiencies.